CREATING A CASHIER APPLICATION WITH ANDROID-BASED QRIS PAYMENT METHOD INTEGRATION - Gilang Virnando; Mochamad Alfan Rosid; Ade Eviyanti Hamzah Setiawan (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to develop an Android-based cashier application integrated with the Quick Response Code Indonesian Standard (QRIS) payment system to enhance transaction efficiency and digital adoption among Micro, Small, and Medium Enterprises (MSMEs). Method: The application was designed and implemented using the Dart programming language with the Flutter framework, employing SQLite as a local database for transaction data management. Results: The findings demonstrate that the application effectively improves MSME operational efficiency, minimizes errors in transaction recording, and facilitates the use of modern digital payment systems. The integration of QRIS supports smoother financial transactions and accelerates the transition toward digital business operations. Novelty: This study presents an innovative digital solution tailored for MSMEs, promoting financial inclusion and competitiveness in the digital economy through a practical, user-friendly, and efficient mobile application.